Biocompatible calcium phosphate-based ceramics and composites - Díaz-Cuenca, Aránzazu; Rabadjieva, Diana; Sezanova, Kostadinka; Gergulova, Rumyana; Ilieva, Radost; Tepavitcharova, Stefka (Materials today : proceedings, 2022)
Synthetic calcium phosphate (CaP) ceramics and composites are used for medical application because of their outstanding biological performance. Although they are the subject of intensive research, so far no material has been obtained with the unique properties of human bones and teeth. This work review recent author strategies using simulated body fluid media synthesis to obtain novel biomimetic CaPs, as well as the combination of supramolecular self-assembly using non-ionic block copolymers and sol-gel chemistry of alcoxysilanes, to obtain silica-CaP composites with remarkable textural properties applicable to dentistry and orthopedics.